Numerical Modeling of Soil Embankment on Soft Soil Using Variation of Expanded Polystyrene (EPS) Geofoam Material Type - Sahrul R., Mohammad (Indonesian Journal Publisher, 2024)
Subgrade is the layer of soil that lies beneath the pavement. The subgrade plays an important role in supporting and spreading the load from the pavement to the underlying soil. Terzaghi, et al. (1967) state that soft soils can pose serious challenges in geotechnical engineering, due to their tendency to experience large settlement under structural loads. Handling soft soils often requires specialized methods such as preloading, vacuum consolidation, or the use of geosynthetics to improve stability. One of the geosynthetics used in handling soft soil is Expanded Polystyrene (EPS) Geofoam. This research aims to determine the settlement behavior of soil embankment on soft soil reinforced with EPS geofoam. The settlement behavior was obtained with the help of GeoStudio software. EPS geofoam has been used since 1960, this material weighs about 1% of the soil weight and less than 10% of the weight of other embankment materials. As a lightweight embankment material, EPS geofoam can reduce the load imposed on the embankment structure. Modeling of soil embankment on soft soil using various types of EPS geofoam material in this research uses GeoStudio software. The modeling analysis uses SIGMA/W in GeoStudio. Numerical modeling of variations in the type of EPS geofoam material in the embankment on soft soil gives the results of a decrease that is not too significant. The settlement results from modeling with GeoStudio are 0.33240 m for EPS 22, 0.33264 m for EPS 29, 0.33323 mm for EPS 39. EPS 39 provides 0.25% higher settlement than EPS 22.